Carbon Dots: A New Type of Carbon-Based Nanomaterial with Wide Applications - Liu, Junjun; Li, Rui; Yang, Bai (ACS central science, 2020)
Carbon dots (CDs), as a new type of carbon-based nanomaterial, have attracted broad research interest for years, because of their diverse physicochemical properties and favorable attributes like good biocompatibility, unique optical properties, low cost, ecofriendliness, abundant functional groups (e.g., amino, hydroxyl, carboxyl), high stability, and electron mobility. In this Outlook, we comprehensively summarize the classification of CDs based on the analysis of their formation mechanism, micro-/nanostructure and property features, and describe their synthetic methods and optical properties including strong absorption, photoluminescence, and phosphorescence. Furthermore, the recent significant advances in diverse applications, including optical (sensor, anticounterfeiting), energy (light-emitting diodes, catalysis, photovoltaics, supercapacitors), and promising biomedicine, are systematically highlighted. Finally, we envisage the key issues to be challenged, future research directions, and perspectives to show a full picture of CDs-based materials.